Faktor Kriminogen Dalam Kasus Penyelundupan Benih Lobster - Handoyo, Iqbal Septiaji; Azkia, Tsania Nurul; Fitriono, Riska Andi (Sekolah Tinggi Ilmu Hukum Muhammadiyah Takengon, 2021)
AbstactIndonesia is the largest archipelagic country in the world which has a wide sea and this also separates one island from another. This is a blessing. However, on the other side of the grace and wealth of marine wealth there are taboos in it. Of course this violates the Constitution of the Republic of Indonesia, which uses this fishery wealth for the prosperity of the people. In addition, a new sub-theme appears that discusses how to take preventive and repressive measures to this fishery case. So that the prosperity of the people is achieved.Keywords : Criminology, Crime, and fisheries